Application of expert system for determining export quality pepper seeds using website-based forward chaining method - Muslihudin M.; Hemalatha S.; Shankar K.; Perumal E.; Nofiyanti; Abadi S.; Hashim W.; Maseleno A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
The need for information about determining export quality pepper seeds is currently needed, this usually occurs in areas far from settlements, one of which is farmers located in rural areas far from technological developments, lack of experts or experts in the surrounding environment. increasingly triggered crop failure rates due to lack of knowledge. by building expert systems whose data is obtained from experts so that the system built has the ability to provide solutions such as an expert who is an expert in their field. This process continues until it reaches a goal or there are no rules whose premise matches the known facts. Media system maker application uses the language of PHP and MySQL as a database. Therefore the author will review how to determine quality export pepper seeds, the implementation of an expert system determines export quality pepper seeds which are expected to provide easy access for users, through the use of website-based media. BEIESP.